Curcumin Nanoformulation for Pulmonary Drug Delivery - Sandy Vitria Kurniawan; Jeanne Adiwinata Pawitan* (Iranian Society of Pharmacognosy, 2022)
Curcumin has various beneficial effects on human health, but its efficacy is yet to be proven in clinical trials. Curcumin has poor bioavailability, low solubility, and rapid metabolism which become the principal reasons behind the lack of curcumin efficiency in clinical trials. This review aimed to focus on nanotechnologies to improve the bioavailability of curcumin inhalation formulations. Many studies were done to improve curcumin's bioavailability by administering through nanoparticle drug carriers. Pulmonary drug delivery has some advantages such as giving a rapid onset of action and bypassing the first hepatic metabolism. Lungs also have a large area for absorption. So far, there are various methods to produce curcumin nanoformulations that are proper, stable, and effective, and are suitable to enhance curcumin pulmonary delivery in the form of liposomes, polymeric and solid lipid nanoparticles, nano suspensions, and cyclodextrin formulations. Therefore, analysis of the various methods, to conclude the best method for curcumin pulmonary delivery is needed. In conclusion, the best method to make nanocurcumin formulation is the one that gives the most advantage and lowest toxicity. Therefore the best choices for curcumin nanoformulations are curcumin nanosuspension and cyclodextrin formulated nanocurcumin/proliposomes.